Paul, the letter writer - Stirewalt, M. Luther, 1913- (Grand Rapids, MI Eerdmans, 2003)
Includes bibliographical references and index.
Keywords: Bible. N.T. Epistles of Paul -- criticism, interpretation, etc; Bible. N.T. Epistles of Paul -- language, style